2021
DOI: 10.1111/bcp.14919
|View full text |Cite
|
Sign up to set email alerts
|

Does the intact nephron hypothesis provide a reasonable model for metformin dosing in chronic kidney disease?

Abstract: This research explored the intact nephron hypothesis (INH) as a model for metformin dosing in patients with chronic kidney disease (CKD). The INH assumes that glomerular filtration rate (GFR) will account for all kidney drug handling even for drugs eliminated by tubular secretion like metformin. We conducted two studies: (1) a regression analysis to explore the relationship between metformin clearance and eGFR metrics, and (2) a joint population pharmacokinetic analysis to test the relationship between metform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Even for drugs eliminated by tubular secretion, such as metformin, the relationships between metformin renal clearance rates and eGFR values are linear. [15] Other researchers have reported that the variability in cefepime trough concentrations are largely explained by eGFR [16,17]. Li A et al believe that individualized use of AMI based on renal function is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Even for drugs eliminated by tubular secretion, such as metformin, the relationships between metformin renal clearance rates and eGFR values are linear. [15] Other researchers have reported that the variability in cefepime trough concentrations are largely explained by eGFR [16,17]. Li A et al believe that individualized use of AMI based on renal function is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst metformin is mainly eliminated by tubular secretion, the relationship between metformin renal clearance and eGFR metrics was recently found to be linear. 31 Therefore, this would support the development of a proportional dose reduction strategy based on GFR in patients with CKD. 32 Also, the evidence from a systematic review of 15 observational studies regarding the safety of metformin in people undergoing dialysis is inconclusive.…”
Section: Metforminmentioning
confidence: 94%